Estudo dos mecanismos de alcalinização intestinal em fêmeas de Lutzomyia longipalpis (Diptera:Psychodidae) - Denise Barguil Nepomuceno (2019)
Lutzomyia longipalpis is a well-known Diptera for its role as the main vector of Leishmania parasites in America. Considering the development of Leishmania is restricted to the sand flies’ gut, studies regarding the digestive physiology of these insects, specially pH regulation, become essential. The mechanisms involved in the process of midgut’s alkalization, which is triggered when females take a blood meal, are not completely elucidated. It is known that ionic transport, a common event in intestinal cells, also associated to membranes energization, nutrients transport and with pH control, may be activated through signaling by second messengers. Amino acids transporters are essential for the digestive physiology of hematophagous diptera and, considering that. Besides, the TOR pathway, an intracellular signaling system highly conserved among eukaryotes, is especially activated in the presence of amino acids; considering blood digestion is, basically, an enzymatic process and provides a great increase in amino acids concentration, it may be activated a consequence of hematophagy and have a potential role in the alkanization of abdominal midgut. Thus, this work aimed to study the mechanisms involved in the control of intestinal alkalinization in L. longipalpis females. From ex-vivo preparations of acidic midguts (pH≤6), previously stained with Bromothymol blue, we found that the treatment with an amino acids solution stimulated the alkalinization of the midguts, but the intensity of the process varied in accordance with the concentration of the solution. When developing a method more accurate to evaluate intestinal pH changes in the presence of amino acids, we decided to use fluorescein dye, whose emission of fluorescence varies with the pH of the medium. In opened midguts, where the dye was present only in the cytoplasm of enterocytes, the presence of amino acids stimulated a significant reduction in fluorescence emission, showing precisely that H+ ions were transported from intestinal lumen to enterocyte’s cytoplasm, leading to the acidification of this compartment. In unopened midguts, the presence of amino acids led to an increase in fluorescence emission, which is in agreement with the fact that intracellular acidification necessarily implies in the alkalization of intestinal lumen. The investigation of the involvement of amino acids transporters allowed the identification of LULOPAT1, a transporter specialized in the symport of amino acids and H+ ions, which is present only in the midgut and has its expression modulated by the nutritional status of the insect: it increases significantly in the first hours after a blood meal. LULOPAT1 is located in the apical side of the midgut, which agrees with our observation that, only in opened midguts, the presence of amino acids in the intestinal lumen was possible, resulting in the acidification of enterocyte’s cytoplasm. Other types of transporters are involved in the entrance of the amino acids by the basolateral membrane, and will be investigated further. The evaluation of ATPases role in energizing membranes in blood fed females showed that the main eletrogenic pump related would be Na+ /K+ -ATP. In the presence of ouabain, a specific inhibitor of Na+ /K+ - ATPase, total enzymatic activity reduced from 1,186±0,340µmol PO4 3− h −1 to 0,416±0,0596µmol PO4 3− h −1 (p<0,05), indicating that this pump was responsible for more than 60% of the total anzymatic activity assayed. Through the evaluation of the effect of the hemolymph from blood fed females in intestinal pH, we verified that hemolymph collected 0- 3 hours after blood feeding was an intense stimulus to alkalization when compared to that collect 30-33 hours after blood feeding. In later stages of blood digestion, the concentration of alkalizing hormones would decrease, but the activity of proteolytic enzymes would at its maximum, with a higher proportion of amino acids being absorbed by the enterocytes, which, then, would be responsible for maintaining an alkaline pH until the end of digestion. Analyzing the involvement of TOR pathway in the control of intestinal pH, we first identified the sequence of 4E-BP gene, one of the main downstream targets of TOR, in the midguts of L. longipalpis. TOR activation necessarily implies in 4E-BP phosphorylation, and western blotting experiments with the antibody Phospho-4E-BP1 (Thr37/46) showed the protein was highly 21 phosphorylated in the first hours after a blood meal. The possible relation between TOR activation and the alkalization induced in the presence of amino acids and in the presence of hemolymph was investigated using acidic intestines (pH≤6), stained with Bromothymol blue, previously treated with rapamycin, an specific inhibitor of TOR pathway. Inhibition of TOR did not affected the efficacy of amino acids inducing alkalization, but strongly interfered in the action of hemolymph on pH, suggesting that pH increase mediated by amino acids occurs through systems others than TOR. When investigating the possible participation of cAMP and cGMP in the regulation of intestinal pH, using ex-vivo preparations of acid intestines (pH≤6), stained with Bromotimol bluewe found that the presence of cAMP induced intestinal alkalinization, while cGMP did not produce any changes. On the other hand, in alkalized intestines, by prior treatment with inactivated serum, cAMP did not changed intestinal pH, which, in the presence of cGMP, became prominently acidic. This study unveiled mechanisms that actively participate in the regulation of intestinal pH, and proposed new pathways that may influence in this process, greatly expanding the existing knowledge regarding the digestive physiology of L. longipalpis. We expect in a near future to develop a working model that addresses all the mechanisms involved in intestinal pH control in L. longipalpis.